Proceso de atención en los estudiantes de Bachillerato de la Unidad Educativa “Cap. Edmundo Chiriboga” Riobamba 2016-2017. - Chimbolema Pilataxi, Ana Lucía (2017)
The research was carried out in the Educational Unit “Cap. Edmundo Chiriboga” with the participation of the students of first year of bachelorship, parallels “A”-“B”-“C” of the city of Riobamba in the Province of Chimborazo during the period 2016-2017, its purpose was to determine the levels of attention; it is known that this process is important so that the student has the ability to focus on a single aspect to the environment or activity and thus improve aducation, was based on conceptualizations provided by different authors where our variable is discussed methodologically, a non-experimental research was proposed since the situation was observed as it was manifested, the type or research was field-bibliographic – transversal, the level of research is exploratory – descriptive, the simple is non – probabilistic – intentional in which participated 112 students, the techniques used to measure the level of care was the psychological test called d2 by Rolf Brickenkamp, to know what are the factors involved in this process was applied a survey formed by five ítems, after performing the analysis and interpretation of results was determined, the level of attention was médium high – High, the factors that intervened in the same are both external and internal, knowing in this way that both high and low level students need to use strategies to maintain and stimulate the process of attention in the classroom.